Activation studies of the α- and β-carbonic anhydrases from the pathogenic bacterium Vibrio cholerae with amines and amino acids. (1st January 2018) - Angeli, Andrea; Del Prete, Sonia; Osman, Sameh M.; Alasmary, Fatmah A. S.; AlOthman, Zeid; Donald, William A.; Capasso, Clemente; Supuran, Claudiu T.
Abstract: The α- and β-class carbonic anhydrases (CAs, EC 4.2.1.1) from the pathogenic bacterium Vibrio cholerae, VchCAα, and VchCAβ, were investigated for their activation with natural and non-natural amino acids and amines. The most effective VchCAα activators were L-tyrosine, histamine, serotonin, and 4-aminoethyl-morpholine, which had KA s in the range of 8.21–12.0 µM. The most effective VchCAβ activators were D-tyrosine, dopamine, serotonin, 2-pyridyl-methylamine, 2-aminoethylpyridine, and 2-aminoethylpiperazine, which had KA s in the submicromolar – low micromolar range (0.18–1.37 µM). The two bacterial enzymes had very different activation profiles with these compounds, between each other, and in comparison to the human isoforms hCA I and II. Some amines were selective activators of VchCAβ, including 2-pyridylmethylamine (KA of 180 nm for VchCAβ, and more than 20 µM for VchCAα and hCA I/II). The activation of CAs from bacteria, such as VchCAα/β has not been considered previously for possible biomedical applications. It would be of interest to study in more detail the extent that CA activators are implicated in the virulence and colonisation of the host by such pathogenic bacteria, which for Vibrio cholerae, is highly dependent on the bicarbonate concentration and pH in the surrounding tissue.